Strategi Mengatasi Common Measures Bias dalam Balanced Scorecard - Sekar Akrom Faradiza; Vera Desy Nurmalia (Telaah Bisnis, 2016)
AbstractBalanced Scorecard (BSC) is a comprehensive performance measurement. BSC is not only used financial indicators but also non financial indicators there are customer, internal process business and learning and growth perspective. By using BSC, evaluators have common and unique measures. When evaluate manager performance, evaluator tends to only use common measures and ignore unique measures. This is called common measures bias. This study aims to investigate whether dissaggregated and aggregated BSC and management communication can overcome common measures bias and intent to BSC approach. This study also will evaluate whether these approach will affect evaluator decision when allocated compensation. We conduct 2x2x2 experiment of undergraduate accounting students. Participant act as a senior manager and evaluate the performance of two divisions and then allocated the bonus. ANOVA repeated measurement are used to conduct hypothesis test. The results showed that dissaggregated BSC and management communication could not overcome common measures bias but effected  management decision when allocated compensation.